Indirect protection in adults ≥18 years of age from pediatric pneumococcal vaccination: a review - Elmira Flem; Celine Mouawad; Arto A. Palmu; Heather Platt; Kelly D. Johnson; E. David McIntosh; Jacobo Abadi; Ulrike K. Buchwald; Kristen Feemster (Expert Review of Vaccines)
Introduction Infant immunization programs using pneumococcal conjugate vaccines (PCVs) have reduced the rates of pneumococcal disease through direct vaccine-induced protection in vaccinated children and through indirect protection in non-vaccinated children and adults.Areas covered This review summarizes current evidence on the indirect protection of adults conferred by pediatric pneumococcal vaccination, including the impact on invasive pneumococcal disease (IPD) incidence and mortality, pneumonia admissions, and nasopharyngeal carriage prevalence. Factors affecting indirect protection against IPD are also discussed.Expert opinion Pediatric immunization with PCVs has substantially decreased vaccine-serotype IPD and pneumonia through indirect protection in both older (≥65 years of age) and younger adults, including those with underlying medical conditions. However, serotype replacement by non-vaccine serotypes, the persistence of some vaccine serotypes, and divergence of serotypes between children and adults have limited the impact of pediatric PCV programs on adult populations. Designing complementary vaccines that leverage indirect protection from pediatric immunization and target the most prevalent adult serotypes may be a preferred strategy to maximize the public health impact of pneumococcal vaccination.